Antimicrobial photodynamic therapy compared to systemic antibiotic therapy in non-surgical treatment of periodontitis: Systematic review and meta-analysis - Souza, Eduardo Quintão Manhanini [UNESP]; da Rocha, Tiago Esgalha [UNESP]; Toro, Luan Felipe [UNESP]; Guiati, Isabella Zacarin [UNESP]; Ervolino, Edilson [UNESP]; Garcia, Valdir Gouveia; Wainwright, Mark; Theodoro, Letícia Helena [UNESP] (Elsevier, 2020)
Background: Periodontitis is one of the most prevalent inflammatory diseases in humans. It is associated with the presence of bacteria and is mediated by the host's immune response This study represents a systematic review and meta-analysis trying to answer the following question: “What is the effect of antimicrobial photodynamic therapy (aPDT) as an adjunct to scaling and root planing (SRP) compared to systemic antibiotic therapy with amoxicillin plus metronidazole (AMX+MTZ) on the non-surgical treatment of periodontitis?”. Methods: Clinical studies comparing aPDT with systemic use of AMX+MTZ were searched until January of 2020 using the databases: PubMed, MEDLINE, SCOPUS, EMBASE, Cochrane Central, Web of Science and Scielo, as well manual searches in related journals. Periodontal clinical parameters such as probing depth (PD), clinical attachment level (CAL) and bleeding on probing (BOP) were statistically analyzed. Results: Five randomized clinical studies (RCTs) were included within the eligibility criteria, and served as a basis for qualitative and quantitative analyzes. All the studies reported an improvement in the clinical parameters with both therapies, although in a direct comparison, our analyzes did not find statistical differences that indicate the superiority of one supporting treatment in relation to the other. Conclusion: Although the limited number of RCTs and the great heterogeneity between them, it can be concluded that aPDT presents similar clinical results compared to antibiotic therapy with AMX+MTZ as adjuvants in the non-surgical treatment of periodontitis.
Keywords: Amoxicillin; Antimicrobial Photodynamic Therapy; Metronidazole; Periodontitis; Photodynamic therapy